Finite strain finite element formulation of coupled solid-fluid mixture for dynamic problems - Bhuddarak Charatpangoon (2018)
© 2018, Int. J. of GEOMATE. Currently, finite element codes for small-strain have been widely applied in geotechnical engineering problems. However, the limitations of these codes are recognized, especially when the strain is large. To overthrow such limitations, finite-strain finite element code for porous media is needed. Therefore, this study aims to implement the finite element code for coupled solid-fluid at finite strain for static and dynamic problems. Firstly, the governing equation for porous media at finite-strain was introduced. Then, the mixed formulation of both phases with respect to the reference coordinates by deriving the governing equations with respect to the reference or current coordinates and by considering the solid and fluid as separate, was given. At present, the code is developed only for elastic regime as its preliminary step. In this study, the proposed code has been verified with the static and dynamic problem. And, the result of the finite-strain finite element code is then compared with the result of the analytical solution and small-strain finite element code within the small-strain regime. Thereafter, the proposed code was used to estimate the response of the earthen dam when subjected to a dynamic load. Finally, the results, discussion, and comparison between small- and finite-strain finite element analyses were presented.